A Carbon-Support-Free Titanium Oxynitride Catalyst for Proton Exchange Membrane Fuel Cell Cathodes. (1st October 2016) - Chisaka, Mitsuharu; Ando, Yuta; Yamamoto, Yusuke; Itagaki, Noriaki
Graphical abstract: Abstract: Cathode catalysts without platinum group metals (PGMs) or carbon supports can reduce the price of proton exchange membrane fuel cells in automobiles, making them commercially competitive. In this paper, an inexpensive and PGM-free catalyst–amorphous nitrogen-doped TiO2 -shell on TiN-core– was synthesized without carbon support. While existing PGM-free all-oxide catalysts without carbon support have shown moderate current densities (at the order of μA/cm 2 ), the current density of this new catalyst is three orders of magnitude higher. Replacing commercial carbon support by hydrothermally synthesized Ti4 O7 significantly enhanced the activity to be close to that of carbon-supported platinum. Although its conductivity and surface area were not sufficient for an accurate evaluation of its activity, these new results demonstrate the possibility of high-performance non-PGM catalysts without carbon supports.